Nanocrystal potassium-doped tungsten material and preparation method thereof

By adding dopants to ammonium tungstenate and using titanium nitride @ chopped tungsten fibers and hafnium diboride as synergists, the nanocrystalline potassium doped tungsten material was optimized, and the crystallization of potassium doped tungsten material during processing was solved. The problems of coarseness and low potassium content have achieved high strength, good plasticity and long service life.

CN119304197AActive Publication Date: 2025-01-14QINGDAO HUATUNGSTEN NEW MATERIAL CO LTD

Patent Information

Application Number
CN202411458417.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-14
Estimated Expiration
2044-10-18

AI Technical Summary

Technical Problem

The existing potassium-doped tungsten materials have problems such as coarse crystallization and low potassium content in rolling processing, resulting in cracking and low yield, which affects service life.

Method used

Using ammonium tungstate as raw material, adding dopants through spraying, optimizing the reduction, mixing and sintering process, preparing nanocrystalline potassium-doped tungsten material, combining titanium nitride @ chopped tungsten fibers and hafnium diboride as synergists, Achieve a small and evenly distributed diffuse phase.

Benefits of technology

It improves the strength, plasticity and high-temperature performance of potassium-doped tungsten materials, extends the service life, and enhances the rolling yield and high-temperature stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005091141110000111
    Figure BDA0005091141110000111
  • Figure BDA0005091141110000121
    Figure BDA0005091141110000121
Patent Text Reader

Abstract

The invention belongs to the technical field of powder metallurgy, and particularly discloses a nanocrystal potassium-doped tungsten material and a preparation method thereof.The preparation method comprises the following steps that ammonium paratungstate is put into spray granulation equipment, then a dopant aqueous solution is added, mixing and drying are conducted, potassium-doped APT is obtained, pre-reduction is conducted through a converter, ammonium tungsten bronze is obtained, and the nanocrystal potassium-doped tungsten bronze is obtained; the method comprises the following steps: carrying out one-step reduction on ammonium tungsten bronze through a fifteen-tube furnace to prepare potassium-doped D powder, carrying out two-step reduction on the ammonium tungsten bronze through the fifteen-tube furnace to prepare potassium-doped B powder, then cleaning with hydrochloric acid and hydrofluoric acid, cleaning with water, filtering, dewatering, drying, crushing and sieving to obtain washed potassium-doped D powder and washed potassium-doped B powder, mixing the washed potassium-doped D powder and washed potassium-doped B powder to obtain mixed powder, and sintering the mixed powder to obtain the potassium-doped B powder. And carrying out isostatic pressing treatment to obtain a tungsten green body, and sintering the tungsten green body in a medium-frequency induction sintering furnace to obtain the tungsten ceramic. The nanocrystal potassium-doped tungsten material has the advantages of high strength, good plasticity, stable high-temperature performance and the like, and a product processed by the nanocrystal potassium-doped tungsten material is long in service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of powder metallurgy, and in particular relates to a nanocrystalline potassium-doped tungsten material and a preparation method thereof. Background Art

[0002] Tungsten is a metal with excellent physical properties. It is silvery white and looks like steel. It has the highest melting point among all metals, and has low saturated vapor pressure, low thermal expansion coefficient, high thermal strength, and good thermal and electrical conductivity. These characteristics make tungsten widely used under special conditions such as high temperature and high pressure, wear resistance, corrosion resistance, and strong radiation. However, pure tungsten material has limitations in some applications, mainly because of its high recrystallization temperature and its ductile-brittle transition temperature, and poor plasticity, which makes processing relatively difficult.

[0003] In order to overcome these limitations, doping and dispersion strengthening of tungsten-based materials is an effective method to improve performance. For example, on the basis of traditional powder metallurgy and forming processing technology, the use of potassium, oxides, carbides or nitrides can effectively improve the processing performance of tungsten materials, improve plasticity and high-temperature strength, etc. Among them, potassium-doped tungsten materials are currently important materials for various heating components, high-precision medical and detection tungsten devices. By doping a trace amount of potassium in tungsten to improve the performance of the material, it shows densification and thermal conductivity compatible with pure tungsten. Potassium doping leads to a significant increase in the hardness of the sintered and deformed states. Although potassium-doped tungsten materials have shown many excellent properties, they still face some challenges in practical applications. For example, the existing potassium-doped tungsten materials have coarse crystals and low potassium content, which may cause cracking during rolling processing, reduce the yield rate, and affect the service life of the final heating components. Therefore, achieving a fine and evenly distributed dispersed phase is the key to obtaining high-performance tungsten materials.

[0004] Chinese patent CN105903977A discloses a method for producing potassium-doped tungsten powder and a method for producing tungsten bars using the tungsten powder. The method comprises the following steps: adding silicon, aluminum and potassium components to blue tungsten powder, using one or two hydrogen reductions to generate doped tungsten powder, and then alkali washing and acid washing the tungsten powder; pressing the doped tungsten powder after the above treatment into billets under high pressure and strength conditions; placing the pressed billets in a molybdenum boat and pre-sintering at high temperature under hydrogen protection conditions: placing the pre-sintered billets in a vertical melting furnace, heating them according to a program under hydrogen protection conditions until the tungsten bars are densely metallized, and the patent adopts alkali washing and acid washing instead of hydrofluoric acid washing, avoiding the use of hydrofluoric acid, causing less pollution to the environment, and having good powder dispersion. The finished tungsten bars have moderate potassium content and good deep processing performance. Chinese patent CN108274017A discloses A potassium-doped tungsten plate and a preparation method thereof are disclosed, the method comprising the following steps: adding potassium silicate and aluminum nitrate solution into a container containing tungsten oxide according to a weight ratio, mixing and drying to obtain doped tungsten oxide; reducing the doped tungsten oxide obtained above to obtain doped tungsten powder; pickling the doped tungsten powder obtained above to obtain a potassium content of 80-160ppm, a silicon content of 154-281ppm, and an aluminum content of not more than 49ppm; drying, pressing, and sintering the pickled tungsten powder to obtain a potassium-doped tungsten plate; the potassium-doped tungsten plate prepared by the patent has good high-temperature deformation resistance and room-temperature bending resistance after rolling, and the performance of the product prepared by the patent is better than that of the product made of pure tungsten plate; however, the potassium-doped tungsten material disclosed in the above patent still has some shortcomings, and its comprehensive performance such as plasticity, processability, and service life needs to be improved. Summary of the invention

[0005] In view of the deficiencies in the above-mentioned prior art, the present invention aims to provide a nanocrystalline potassium-doped tungsten material, which uses ammonium tungstate as a raw material, adds a dopant by spraying, and efficiently prepares the nanocrystalline potassium-doped tungsten material by optimizing the reduction, mixing and sintering processes, and has the advantages of high strength, good plasticity, stable high-temperature performance, etc. The processed product has a long service life. The present invention also provides a preparation method of the above-mentioned nanocrystalline potassium-doped tungsten material.

[0006] A method for preparing a nanocrystalline potassium-doped tungsten material comprises the following steps:

[0007] Step I, 300-500 parts by weight of ammonium paratungstate (APT) are placed in a spray granulation device, and an appropriate amount of potassium hydroxide, aluminum nitrate, and potassium silicate are added to 5-20 parts by weight of water to form a doping agent aqueous solution, and the doping agent aqueous solution is added to the ammonium paratungstate by spraying, stirred and mixed, steam dried, and the vacuum degree in the equipment is maintained at -0.02 to -0.05Mpa to obtain potassium-doped APT, and pre-reduced by a converter at 400-500°C in a hydrogen atmosphere until the reduction is completed to obtain ammonium tungsten bronze;

[0008] Step II, 50-150 parts by weight of the ammonium tungsten bronze obtained in step I is passed through a fifteen-tube furnace at 800-900° C. to prepare potassium-doped D powder with a particle size of 3.2-3.5 μm;

[0009] Step III, 50-150 parts by weight of the ammonium tungsten bronze obtained in step I is passed through a fifteen-tube furnace at 600-700° C. to prepare tungsten oxide with a particle size of 2.5-2.8 μm, and then passed through a fifteen-tube furnace at 800-900° C. to prepare potassium-doped B powder with a particle size of 2.4-2.7 μm;

[0010] Step IV, respectively washing the potassium-doped D powder obtained in step II and the potassium-doped B powder obtained in step III with 3-6% hydrochloric acid and 3-6% hydrofluoric acid by mass to remove invalid potassium, silicon, aluminum and other impurities, then washing with water for 1-3 times, filtering and removing water with anhydrous ethanol, vacuum drying, crushing and sieving, and obtaining washed potassium-doped D powder and washed potassium-doped B powder respectively;

[0011] Step V, mixing 40-60 parts by weight of washed potassium-doped D powder and 40-60 parts by weight of washed potassium-doped B powder obtained in step IV to obtain a mixed powder, and then cold isostatic pressing at 130-160 MPa for 150-200 seconds to obtain a tungsten green body;

[0012] Step VI: Place the tungsten green body obtained in step V into a medium frequency induction sintering furnace, introduce hydrogen simultaneously from top to bottom, and sinter at 2000-2100° C. for 5-10 hours to obtain the nanocrystalline potassium-doped tungsten material.

[0013] Preferably, the dopant aqueous solution in step I contains 0.2-0.4% potassium oxide, 0.001-0.003% aluminum oxide, and 0.3-0.5% silicon dioxide in weight percentage relative to the weight of ammonium paratungstate, calculated on an equivalent basis.

[0014] Preferably, the washed potassium-doped D powder obtained in step IV is a washed potassium-doped D powder having a particle size of 3.2-3.5 μm, a potassium content of 60-80 ppm, and an oxygen content of less than 100 ppm.

[0015] Preferably, the washed potassium-doped B powder obtained in step IV is a washed potassium-doped B powder having a particle size of 2.4-2.7 μm, a potassium content of 160-200 ppm, and an oxygen content of less than 100 ppm.

[0016] The present invention applies nanotechnology to the manufacture of potassium-doped tungsten materials. Through the spray granulation of APT and a dopant, the combination of potassium-doped B powder and potassium-doped D powder is used to achieve medium-frequency low-temperature and efficient sintering. The prepared potassium-doped tungsten material has a moderate effective potassium content, and potassium is not only evenly distributed in the tungsten powder, but also has a better bonding effect. The crystal structure reaches the nanometer level, the rolling product rate is high, and the high-temperature resistance is better. It shows better high-temperature stability in heating components, high-precision medical and detection tungsten devices, and has the advantages of long service life and high processing efficiency.

[0017] Preferably, in step V, a synergist is also added and mixed with the washed potassium-doped D powder and the washed potassium-doped B powder.

[0018] Preferably, the amount of the synergist added is 1-5 parts by weight; further preferably, the amount of the synergist added is 2-3 parts by weight.

[0019] Preferably, the synergist is composed of titanium nitride@chopped tungsten fiber and hafnium diboride in a weight ratio of 10:1-5.

[0020] Preferably, the preparation method of the titanium nitride@chopped tungsten fiber is:

[0021] The short-cut tungsten fibers are added to anhydrous ethanol at a solid-liquid ratio of 1g:5-10mL, and ultrasonically treated for 30-50min, filtered, and vacuum dried to obtain pretreated short-cut tungsten fibers; 10-20 parts by weight of the pretreated short-cut tungsten fibers are placed on a base disc, and a precursor is introduced for vapor deposition. The deposition time is 3-5h and the deposition temperature is 500-700°C to obtain titanium nitride@short-cut tungsten fibers.

[0022] Preferably, the chopped tungsten fiber is prepared by chopping tungsten fiber with a diameter of 100-200 μm and a tensile strength of 2.5-4 GPa into 1-3 mm.

[0023] Preferably, the precursor is composed of gaseous titanium tetrachloride and ammonia, wherein the flow ratio of gaseous titanium tetrachloride to ammonia is 1:3-6.

[0024] The present invention adopts titanium nitride @ short-cut tungsten fiber and hafnium diboride as synergists, wherein the self-made titanium nitride @ short-cut tungsten fiber can effectively improve the toughness of the tungsten-based material, and the titanium nitride layer deposited on the fiber surface can make the interface between the fiber and the tungsten matrix present a weak bonding state. When the crack of the tungsten material is extended to the vicinity of the fiber by an external force, this weakly bonded fiber / tungsten-based interface is conducive to the generation of crack deflection / bridging, fiber debonding / pulling out and other energy consumption mechanisms, thereby increasing the energy expansion path and further improving the toughness of the nanocrystalline potassium-doped tungsten material; at the same time, titanium nitride itself has high strength, high hardness, wear resistance, high-temperature chemical stability and high thermal conductivity, which can increase the melting point of the tungsten material, inhibit the growth of grains, make the tungsten material have high density and small grain size, and improve the comprehensive performance and service life.

[0025] Hafnium diboride has the characteristics of high hardness, high melting point, and good electrical and thermal conductivity. During the sintering process, hafnium diboride can be dispersed into the tungsten material to improve its grain boundary toughness, act as a pinning point for dislocations, inhibit lattice slip, and improve the strength and high-temperature wear resistance of the tungsten material; at the same time, hafnium diboride can play a bonding role, promoting the bonding between titanium nitride @ short-cut tungsten fiber doped potassium powder, which is conducive to the formation of uniform and dense tungsten material.

[0026] Beneficial effects of the present invention:

[0027] The present invention uses ammonium tungstate as raw material, adds doping agent by spraying, and optimizes the reduction, mixing and sintering process to efficiently prepare nanocrystalline potassium-doped tungsten materials with the advantages of high strength, good plasticity, and stable high-temperature performance. The average number of grains on the interface is not less than 10,000 / mm 2 The average grain size is less than 10μm, the product has good ductility and a high rolling yield, which can increase the service life of products such as heating components, high-precision medical and detection tungsten devices. DETAILED DESCRIPTION

[0028] The above content of the present invention is further described in detail below in conjunction with specific implementation modes, but this should not be understood as the scope of the above subject matter of the present invention being limited to the following embodiments.

[0029] Example 1

[0030] A method for preparing a nanocrystalline potassium-doped tungsten material comprises the following steps:

[0031] Step I, 400 parts by weight of ammonium paratungstate (APT) are placed in a spray granulation device, and appropriate amounts of potassium hydroxide, aluminum nitrate, and potassium silicate are added to 10 parts by weight of deionized water to form a doping agent aqueous solution, wherein the doping agent aqueous solution contains 0.22% potassium oxide, 0.0015% aluminum oxide, and 0.36% silicon dioxide in terms of weight percentage relative to the weight of ammonium paratungstate according to equivalent calculation, and the doping agent aqueous solution is added to the ammonium paratungstate by spraying, stirred and mixed, steam dried, and the vacuum degree in the equipment is maintained at -0.02 to -0.05Mpa to obtain potassium-doped APT, which is pre-reduced by a converter at 440°C in a hydrogen atmosphere until the reduction is complete to obtain ammonium tungsten bronze;

[0032] Step II, 100 parts by weight of the ammonium tungsten bronze obtained in step I is passed through a fifteen-tube furnace at 860° C. to prepare potassium-doped D powder with a particle size of 3.5 μm;

[0033] Step III, 100 parts by weight of the ammonium tungsten bronze obtained in step I is passed through a fifteen-tube furnace at 680° C. to prepare tungsten oxide with a particle size of 2.5 μm, and then passed through a fifteen-tube furnace at 860° C. to prepare potassium-doped B powder with a particle size of 2.4 μm;

[0034] Step IV, respectively, washing the potassium-doped D powder obtained in step II and the potassium-doped B powder obtained in step III with 5% hydrochloric acid and 5% hydrofluoric acid by mass to remove invalid potassium, silicon, aluminum and other impurities, then washing twice with deionized water, filtering and removing water with anhydrous ethanol, vacuum drying, crushing and sieving, and obtaining washed potassium-doped D powder with a particle size of 3.5 μm, a potassium content of 69 ppm, and an oxygen content of less than 100 ppm and washed potassium-doped B powder with a particle size of 2.4 μm, a potassium content of 184 ppm, and an oxygen content of less than 100 ppm;

[0035] Step V, 50 parts by weight of washed potassium-doped D powder and 50 parts by weight of washed potassium-doped B powder obtained in step IV are mixed to obtain a mixed powder, and then subjected to cold isostatic pressing at 150 MPa for 180 seconds to obtain a tungsten green body;

[0036] Step VI: Place the tungsten green body obtained in step V into a medium frequency induction sintering furnace, add hydrogen from both the top and bottom, and sinter at 2055°C for 7h to obtain the nanocrystalline potassium-doped tungsten material, with an oxygen content of 11ppm, a potassium content of 98ppm, an aluminum content of 18ppm, a silicon content of 7ppm, and a density of 18.5g / cm 3 Three 10μm×10μm areas were selected for observation and mathematical statistics at 5000 times SEM, and the average number of grains was 15000 / mm 2 The average grain size is 9μm. After the above-mentioned nanocrystalline potassium-doped tungsten material is rolled to 5mm for multiple times and made into mosquito coil type heating components, the service life is increased by 2.0 times compared with pure tungsten.

[0037] Comparative Example 1

[0038] A method for preparing a nanocrystalline potassium-doped tungsten material comprises the following steps:

[0039] Step I, 400 parts by weight of ammonium paratungstate (APT) are placed in a spray granulation device, and appropriate amounts of potassium hydroxide, aluminum nitrate, and potassium silicate are added to 10 parts by weight of deionized water to form a doping agent aqueous solution, wherein the doping agent aqueous solution contains 0.22% potassium oxide, 0.0015% aluminum oxide, and 0.36% silicon dioxide in terms of weight percentage relative to the weight of ammonium paratungstate according to equivalent calculation, and the doping agent aqueous solution is added to the ammonium paratungstate by spraying, stirred and mixed, steam dried, and the vacuum degree in the equipment is maintained at -0.02 to -0.05Mpa to obtain potassium-doped APT, which is pre-reduced by a converter at 440°C in a hydrogen atmosphere until the reduction is complete to obtain ammonium tungsten bronze;

[0040] Step II, 100 parts by weight of the ammonium tungsten bronze obtained in step I is passed through a fifteen-tube furnace at 860° C. to prepare potassium-doped D powder with a particle size of 3.5 μm;

[0041] Step III, washing the potassium-doped D powder obtained in step II with 5% hydrochloric acid and 5% hydrofluoric acid in sequence to remove invalid potassium, silicon, aluminum and other impurities, then washing with deionized water twice, filtering and removing water with anhydrous ethanol, vacuum drying, crushing and sieving, and obtaining washed potassium-doped D powder with a particle size of 3.5 μm, a potassium content of 69 ppm, and an oxygen content of less than 100 ppm;

[0042] Step IV, subjecting the washed potassium-doped D powder obtained in step III to cold isostatic pressing at 150 MPa for 180 seconds to obtain a tungsten green body;

[0043] Step V: Place the tungsten green body obtained in step IV into a medium frequency induction sintering furnace, introduce hydrogen simultaneously from top to bottom, and sinter at 2055°C for 7h to obtain the nanocrystalline potassium-doped tungsten material with a density of 17.9 g / cm 3 The above-mentioned nanocrystalline potassium-doped tungsten material is rolled to 5 mm multiple times and made into a mosquito coil type heating element, and its service life is increased by 1.12 times compared with pure tungsten.

[0044] Comparative Example 2

[0045] A method for preparing a nanocrystalline potassium-doped tungsten material comprises the following steps:

[0046] Step I, 400 parts by weight of ammonium paratungstate (APT) are placed in a spray granulation device, and appropriate amounts of potassium hydroxide, aluminum nitrate, and potassium silicate are added to 10 parts by weight of deionized water to form a doping agent aqueous solution, wherein the doping agent aqueous solution contains 0.22% potassium oxide, 0.0015% aluminum oxide, and 0.36% silicon dioxide in terms of weight percentage relative to the weight of ammonium paratungstate according to equivalent calculation, and the doping agent aqueous solution is added to the ammonium paratungstate by spraying, stirred and mixed, steam dried, and the vacuum degree in the equipment is maintained at -0.02 to -0.05Mpa to obtain potassium-doped APT, which is pre-reduced by a converter at 440°C in a hydrogen atmosphere until the reduction is complete to obtain ammonium tungsten bronze;

[0047] Step II, 100 parts by weight of the ammonium tungsten bronze obtained in step I is passed through a fifteen-tube furnace at 680° C. to prepare tungsten oxide with a particle size of 2.5 μm, and then passed through a fifteen-tube furnace at 860° C. to prepare potassium-doped B powder with a particle size of 2.4 μm;

[0048] Step III, washing the potassium-doped B powder obtained in step II with 5% hydrochloric acid and 5% hydrofluoric acid in mass percentage concentration to remove invalid potassium, silicon, aluminum and other impurities, then washing with deionized water twice, filtering and removing water with anhydrous ethanol, vacuum drying, crushing and sieving, and obtaining washed potassium-doped B powder with a particle size of 2.4 μm, a potassium content of 184 ppm, and an oxygen content of less than 100 ppm;

[0049] Step IV, subjecting the washed potassium-doped B powder obtained in step III to cold isostatic pressing at 150 MPa for 180 seconds to obtain a tungsten green body;

[0050] Step V, put the tungsten green body obtained in step IV into a medium frequency induction sintering furnace, use hydrogen to feed both the top and bottom, and sinter at 2055°C for 7 hours to obtain the nanocrystalline potassium-doped tungsten material. The nanocrystalline potassium-doped tungsten material is rolled to 5 mm for multiple times to make a mosquito coil type heating element, and its service life is increased by 1.37 times compared with pure tungsten.

[0051] Example 2

[0052] A method for preparing a nanocrystalline potassium-doped tungsten material comprises the following steps:

[0053] Step I, 400 parts by weight of ammonium paratungstate (APT) are placed in a spray granulation device, and appropriate amounts of potassium hydroxide, aluminum nitrate, and potassium silicate are added to 10 parts by weight of deionized water to form a doping agent aqueous solution, wherein the doping agent aqueous solution contains 0.22% potassium oxide, 0.0015% aluminum oxide, and 0.36% silicon dioxide in terms of weight percentage relative to the weight of ammonium paratungstate according to equivalent calculation, and the doping agent aqueous solution is added to the ammonium paratungstate by spraying, stirred and mixed, steam dried, and the vacuum degree in the equipment is maintained at -0.02 to -0.05Mpa to obtain potassium-doped APT, which is pre-reduced by a converter at 440°C in a hydrogen atmosphere until the reduction is complete to obtain ammonium tungsten bronze;

[0054] Step II, 100 parts by weight of the ammonium tungsten bronze obtained in step I is passed through a fifteen-tube furnace at 860° C. to prepare potassium-doped D powder with a particle size of 3.5 μm;

[0055] Step III, 100 parts by weight of the ammonium tungsten bronze obtained in step I is passed through a fifteen-tube furnace at 680° C. to prepare tungsten oxide with a particle size of 2.5 μm, and then passed through a fifteen-tube furnace at 860° C. to prepare potassium-doped B powder with a particle size of 2.4 μm;

[0056] Step IV, respectively, washing the potassium-doped D powder obtained in step II and the potassium-doped B powder obtained in step III with 5% hydrochloric acid and 5% hydrofluoric acid by mass to remove invalid potassium, silicon, aluminum and other impurities, then washing twice with deionized water, filtering and removing water with anhydrous ethanol, vacuum drying, crushing and sieving, and obtaining washed potassium-doped D powder with a particle size of 3.5 μm, a potassium content of 69 ppm, and an oxygen content of less than 100 ppm and washed potassium-doped B powder with a particle size of 2.4 μm, a potassium content of 184 ppm, and an oxygen content of less than 100 ppm;

[0057] Step V, 50 parts by weight of washed potassium-doped D powder and 50 parts by weight of washed potassium-doped B powder obtained in step IV and 2.5 parts by weight of a synergist are mixed to obtain a mixed powder, and then subjected to a 150 MPa cold isostatic pressing treatment for 180 seconds to obtain a tungsten green body; the synergist is composed of titanium nitride @ chopped tungsten fiber and hafnium diboride (CAS: 12007-23-7) in a weight ratio of 10:3;

[0058] The preparation method of the titanium nitride@short-cut tungsten fiber is as follows:

[0059] Add short-cut tungsten fibers to anhydrous ethanol at a solid-liquid ratio of 1g:7mL and ultrasonically treat for 45min, filter, and vacuum dry to obtain pretreated short-cut tungsten fibers; take 15 parts by weight of pretreated short-cut tungsten fibers and place them on a substrate disc, and introduce a precursor for vapor deposition, the deposition time is 4.5h, and the deposition temperature is 600℃. The precursor is composed of gaseous titanium tetrachloride and ammonia, wherein the flow ratio of gaseous titanium tetrachloride (CAS: 7550-45-0) to ammonia is 1:5, and titanium nitride @ short-cut tungsten fibers are obtained. The short-cut tungsten fibers are made by chopping tungsten fibers with a diameter of 100μm and a tensile strength of 3GPa to 1.5mm;

[0060] Step VI: Place the tungsten green body obtained in step V into a medium frequency induction sintering furnace, introduce hydrogen simultaneously from top to bottom, and sinter at 2055° C. for 7 hours to obtain the nanocrystalline potassium-doped tungsten material.

[0061] Example 3

[0062] A method for preparing a nanocrystalline potassium-doped tungsten material comprises the following steps:

[0063] Step I, 400 parts by weight of ammonium paratungstate (APT) are placed in a spray granulation device, and appropriate amounts of potassium hydroxide, aluminum nitrate, and potassium silicate are added to 10 parts by weight of deionized water to form a doping agent aqueous solution, wherein the doping agent aqueous solution contains 0.22% potassium oxide, 0.0015% aluminum oxide, and 0.36% silicon dioxide in terms of weight percentage relative to the weight of ammonium paratungstate according to equivalent calculation, and the doping agent aqueous solution is added to the ammonium paratungstate by spraying, stirred and mixed, steam dried, and the vacuum degree in the equipment is maintained at -0.02 to -0.05Mpa to obtain potassium-doped APT, which is pre-reduced by a converter at 440°C in a hydrogen atmosphere until the reduction is complete to obtain ammonium tungsten bronze;

[0064] Step II, 100 parts by weight of the ammonium tungsten bronze obtained in step I is passed through a fifteen-tube furnace at 860° C. to prepare potassium-doped D powder with a particle size of 3.5 μm;

[0065] Step III, 100 parts by weight of the ammonium tungsten bronze obtained in step I is passed through a fifteen-tube furnace at 680° C. to prepare tungsten oxide with a particle size of 2.5 μm, and then passed through a fifteen-tube furnace at 860° C. to prepare potassium-doped B powder with a particle size of 2.4 μm;

[0066] Step IV, respectively, washing the potassium-doped D powder obtained in step II and the potassium-doped B powder obtained in step III with 5% hydrochloric acid and 5% hydrofluoric acid by mass to remove invalid potassium, silicon, aluminum and other impurities, then washing twice with deionized water, filtering and removing water with anhydrous ethanol, vacuum drying, crushing and sieving, and obtaining washed potassium-doped D powder with a particle size of 3.5 μm, a potassium content of 69 ppm, and an oxygen content of less than 100 ppm and washed potassium-doped B powder with a particle size of 2.4 μm, a potassium content of 184 ppm, and an oxygen content of less than 100 ppm;

[0067] Step V, 50 parts by weight of washed potassium-doped D powder and 50 parts by weight of washed potassium-doped B powder obtained in step IV and 2.5 parts by weight of a synergist are mixed to obtain a mixed powder, and then subjected to a 150 MPa cold isostatic pressing treatment for 180 seconds to obtain a tungsten green body; the synergist is titanium nitride @ chopped tungsten fiber;

[0068] The preparation method of the titanium nitride@short-cut tungsten fiber is as follows:

[0069] Add short-cut tungsten fibers to anhydrous ethanol at a solid-liquid ratio of 1g:7mL and ultrasonically treat for 45min, filter, and vacuum dry to obtain pretreated short-cut tungsten fibers; take 15 parts by weight of pretreated short-cut tungsten fibers and place them on a substrate disc, and introduce a precursor for vapor deposition, the deposition time is 4.5h, and the deposition temperature is 600℃. The precursor is composed of gaseous titanium tetrachloride and ammonia, wherein the flow ratio of gaseous titanium tetrachloride (CAS: 7550-45-0) to ammonia is 1:5, and titanium nitride @ short-cut tungsten fibers are obtained. The short-cut tungsten fibers are made by chopping tungsten fibers with a diameter of 100μm and a tensile strength of 3GPa to 1.5mm;

[0070] Step VI: Place the tungsten green body obtained in step V into a medium frequency induction sintering furnace, introduce hydrogen simultaneously from top to bottom, and sinter at 2055° C. for 7 hours to obtain the nanocrystalline potassium-doped tungsten material.

[0071] Example 4

[0072] A method for preparing a nanocrystalline potassium-doped tungsten material comprises the following steps:

[0073] Step I, 400 parts by weight of ammonium paratungstate (APT) are placed in a spray granulation device, and appropriate amounts of potassium hydroxide, aluminum nitrate, and potassium silicate are added to 10 parts by weight of deionized water to form a doping agent aqueous solution, wherein the doping agent aqueous solution contains 0.22% potassium oxide, 0.0015% aluminum oxide, and 0.36% silicon dioxide in terms of weight percentage relative to the weight of ammonium paratungstate according to equivalent calculation, and the doping agent aqueous solution is added to the ammonium paratungstate by spraying, stirred and mixed, steam dried, and the vacuum degree in the equipment is maintained at -0.02 to -0.05Mpa to obtain potassium-doped APT, which is pre-reduced by a converter at 440°C in a hydrogen atmosphere until the reduction is complete to obtain ammonium tungsten bronze;

[0074] Step II, 100 parts by weight of the ammonium tungsten bronze obtained in step I is passed through a fifteen-tube furnace at 860° C. to prepare potassium-doped D powder with a particle size of 3.5 μm;

[0075] Step III, 100 parts by weight of the ammonium tungsten bronze obtained in step I is passed through a fifteen-tube furnace at 680° C. to prepare tungsten oxide with a particle size of 2.5 μm, and then passed through a fifteen-tube furnace at 860° C. to prepare potassium-doped B powder with a particle size of 2.4 μm;

[0076] Step IV, respectively, washing the potassium-doped D powder obtained in step II and the potassium-doped B powder obtained in step III with 5% hydrochloric acid and 5% hydrofluoric acid by mass to remove invalid potassium, silicon, aluminum and other impurities, then washing twice with deionized water, filtering and removing water with anhydrous ethanol, vacuum drying, crushing and sieving, and obtaining washed potassium-doped D powder with a particle size of 3.5 μm, a potassium content of 69 ppm, and an oxygen content of less than 100 ppm and washed potassium-doped B powder with a particle size of 2.4 μm, a potassium content of 184 ppm, and an oxygen content of less than 100 ppm;

[0077] Step V, 50 parts by weight of washed potassium-doped D powder and 50 parts by weight of washed potassium-doped B powder obtained in step IV and 2.5 parts by weight of a synergist are mixed to obtain a mixed powder, and then subjected to a 150 MPa cold isostatic pressing treatment for 180 seconds to obtain a tungsten green body; the synergist is hafnium diboride;

[0078] Step VI: Place the tungsten green body obtained in step V into a medium frequency induction sintering furnace, introduce hydrogen simultaneously from top to bottom, and sinter at 2055° C. for 7 hours to obtain the nanocrystalline potassium-doped tungsten material.

[0079] Test Example 1

[0080] The elongation at break of the tensile specimens of the nanocrystalline potassium-doped tungsten materials in the above examples was measured according to the standard GB / T 228.2-2015 at different temperatures. When the elongation at break exceeded 5%, the corresponding test temperature was the tensile toughness-brittle transition temperature. The ultimate tensile strength of the nanocrystalline potassium-doped tungsten materials at 800°C was measured, and 5 groups of each example were paralleled to take the average value.

[0081] Table 1. Transition temperature and tensile strength test results

[0082]

[0083]

[0084] Test Example 2

[0085] The nanocrystalline potassium-doped tungsten materials in the above examples were processed into wires with a diameter of 200 μm, and cut for 300 minutes under the condition of 10.5A current. After the test, the remaining diameter of the wire was measured. Five groups of each example were paralleled and the average value was taken. The larger the remaining diameter after the test, the better the high temperature resistance and wear resistance of the alloy.

[0086] Table 2. High temperature anti-wear performance test results

[0087] Initial diameter / μm Remaining diameter / μm Example 1 200 187 Example 2 200 198 Example 3 200 194 Example 4 200 191

[0088] It can be seen from the above results that the nanocrystalline potassium-doped tungsten material prepared by the present invention has good toughness, strength and high-temperature stability, especially Example 2 simultaneously uses titanium nitride @ chopped tungsten fiber and hafnium diboride as enhancers, wherein the homemade titanium nitride @ chopped tungsten fiber can effectively improve the toughness of the tungsten-based material, and the titanium nitride layer deposited on the fiber surface can make the fiber and the tungsten matrix interface present a weak bonding state. When the crack of the tungsten material is extended to the vicinity of the fiber by external force, this weakly bonded fiber / tungsten-based interface is conducive to the generation of crack deflection / bridging, fiber debonding / pulling out and other energy consumption mechanisms, thereby increasing the energy expansion path and further improving the toughness of the nanocrystalline potassium-doped tungsten material; at the same time, titanium nitride itself has high strength, high hardness, wear resistance, high-temperature chemical stability and high thermal conductivity, which can increase the melting point of the tungsten material, inhibit the growth of grains, make the tungsten material have high density and small grain size, and improve the comprehensive performance and service life. Hafnium diboride has the characteristics of high hardness, high melting point, and good electrical and thermal conductivity. During the sintering process, hafnium diboride can be dispersed into the tungsten material to improve its grain boundary toughness, act as a pinning point for dislocations, inhibit lattice slip, and improve the strength and high-temperature wear resistance of the tungsten material; at the same time, hafnium diboride can play a bonding role, promoting the bonding between titanium nitride @ short-cut tungsten fiber doped potassium powder, which is conducive to the formation of uniform and dense tungsten material.

[0089] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution that can be obtained by a person skilled in the art through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the prior art should be within the scope of protection determined by the claims.

Claims

1. A method for preparing a nanocrystalline potassium-doped tungsten material, characterized in that: The following steps are involved: Step I: put ammonium paratungstate into a spray granulation device, add potassium hydroxide, aluminum nitrate and potassium silicate into water to form a doping agent aqueous solution, add the doping agent aqueous solution into the ammonium paratungstate by spraying, stir and mix, steam dry to obtain potassium-doped APT, and pre-reduce it in a converter at 400-500°C in a hydrogen atmosphere to obtain ammonium tungsten bronze; Step II, the ammonium tungsten bronze obtained in step I is passed through a fifteen-tube furnace at 800-900° C. to prepare potassium-doped D powder with a particle size of 3.2-3.5 μm; Step III, the ammonium tungsten bronze obtained in step I is passed through a fifteen-tube furnace at 600-700° C. to prepare tungsten oxide with a particle size of 2.5-2.8 μm, and then passed through a fifteen-tube furnace at 800-900° C. to prepare potassium-doped B powder with a particle size of 2.4-2.7 μm; Step IV, respectively washing the potassium-doped D powder obtained in step II and the potassium-doped B powder obtained in step III with hydrochloric acid and hydrofluoric acid in sequence, then washing with water, filtering and removing water with anhydrous ethanol, vacuum drying, crushing and sieving, to obtain washed potassium-doped D powder and washed potassium-doped B powder; Step V, mixing the washed potassium-doped D powder and the washed potassium-doped B powder obtained in step IV to obtain a mixed powder, and then subjecting the mixed powder to a cold isostatic pressing treatment at 130-160 MPa for 150-200 seconds to obtain a tungsten green body; Step VI: Place the tungsten green body obtained in step V into a medium frequency induction sintering furnace, introduce hydrogen simultaneously from top to bottom, and sinter at 2000-2100° C. for 5-10 hours to obtain the nanocrystalline potassium-doped tungsten material.

2. The method for preparing the nanocrystalline potassium-doped tungsten material according to claim 1, characterized in that: The dopant aqueous solution in step I contains 0.2-0.4% potassium oxide, 0.001-0.003% aluminum oxide, and 0.3-0.5% silicon dioxide in weight percentage relative to the weight of ammonium paratungstate according to equivalent calculation.

3. The method for preparing the nanocrystalline potassium-doped tungsten material according to claim 1, characterized in that: After washing in step IV, the potassium-doped D powder has a particle size of 3.2-3.5 μm, a potassium content of 60-80 ppm, and an oxygen content of less than 100 ppm.

4. The method for preparing nanocrystalline potassium-doped tungsten material according to claim 1, characterized in that: After washing in step IV, the potassium-doped B powder has a particle size of 2.4-2.7 μm, a potassium content of 160-200 ppm, and an oxygen content of less than 100 ppm.

5. The method for preparing nanocrystalline potassium-doped tungsten material according to claim 1, characterized in that: In step V, a synergist is also added to mix with the washed potassium-doped D powder and the washed potassium-doped B powder.

6. The method for preparing nanocrystalline potassium-doped tungsten material according to claim 5, characterized in that: The synergist is titanium nitride@short-cut tungsten fiber and / or hafnium diboride.

7. The method for preparing nanocrystalline potassium-doped tungsten material according to claim 5, characterized in that: The synergist consists of titanium nitride@short-cut tungsten fiber and hafnium diboride.

8. The method for preparing the nanocrystalline potassium-doped tungsten material according to claim 6 or 7, characterized in that: The preparation method of the titanium nitride@short-cut tungsten fiber is as follows: The short-cut tungsten fibers are added to anhydrous ethanol for ultrasonic treatment, filtered, and vacuum dried to obtain pretreated short-cut tungsten fibers; the pretreated short-cut tungsten fibers are placed on a base disc, and a precursor is introduced for vapor deposition, wherein the precursor is composed of gaseous titanium tetrachloride and ammonia, and titanium nitride@short-cut tungsten fibers are obtained after the deposition.

9. A nanocrystalline potassium-doped tungsten material, characterized in that: The method is prepared by any one of claims 1 to 8.

Citation Information

Patent Citations

  • Production method of potassium-dopedmetal tungsten powder and method for producing tungsten bar through tungsten powder

    CN105903977A

  • Potassium-doped metal tungsten plate and preparation method thereof

    CN108274017A

  • Method for preparing square tungsten-yttrium blank

    CN101406956A

  • Method for producing tungsten bar serving as halogen tungsten lamp tungsten filament

    CN102198507A

  • Manufacturing method of tungsten filament of lamp bulb

    CN1073724A

Cited By

  • High-temperature-resistant tungsten filament and preparation method thereof

    CN120815982A